Triamcinolone acetonide intralesional injection for the treatment of keloid scars: patient selection and perspectives - Morelli Coppola M; Salzillo R; Segreto F; Persichetti P (Dove Medical Press, 2018)
Marco Morelli Coppola,* Rosa Salzillo,* Francesco Segreto, Paolo Persichetti Department of Plastic, Reconstructive and Aesthetic Surgery, “Campus Bio-Medico” University of Rome, Rome, Italy *These authors contributed equally to this work Abstract: Keloids are pathological scars presenting as nodular lesions that extend beyond the area of injury. They do not spontaneously regress, often continuing to grow over time. The abnormal wound-healing process underlying keloid formation results from the lack of control mechanisms self-regulating cell proliferation and tissue repair. Keloids may lead to cosmetic disfigurement and functional impairment and affect the quality of life. Although several treatments were reported in the literature, no universally effective therapy was found to date. The most common approach is intralesional corticosteroid injection alone or in combination with other treatment modalities. Triamcinolone acetonide (TAC) is the most commonly used intralesional corticosteroid. The aim of this article was to review the use of TAC, alone or in combination, in the treatment of keloid scars. The response to corticosteroid injection alone is variable with 50–100% regression and a recurrence rate of 33% and 50% after 1 and 5 years, respectively. Compared to verapamil, TAC showed a faster and more effective response even though with a higher complication rate. TAC combined with verapamil was proved to be effective with statistically significant overall improvements of scars over time and long-term stable results. TAC and 5-fluorouracil (5-FU) intralesional injections were found to achieve comparable outcomes when administered alone, although 5-FU was more frequently associated with side effects. Conversely, the combination of 5-FU and TAC was more effective and showed fewer undesirable effects compared to TAC or 5-FU alone. Several kinds of laser treatments were reported to address keloids; however, laser therapy alone was burdened with a high recurrence rate. Better results were described by combining CO2, pulsed-dye or Nd: YAG lasers with TAC intralesional injections. Further options such as needle-less intraepidermal drug delivery are being explored, but more studies are needed to establish safety, feasibility and effectiveness of this approach. Keywords: keloids, scars, intralesional corticosteroid injections